„Bajki samograjki”, czyli o słuchowiskach i książkach do słuchania w rozwoju mowy dziecka - Osowicka-Kondratowicz, Magdalena (Papers in Linguistics, 2019)
The article describes selected possibilities of using radio plays and audio books in the course of speech therapy and it shows what competencies and skills are shaped during the reception of audio works.